The Effectiveness of Intravitreal Bevacizumab with or without Triamcinolone Acetonide for Diabetic Macular Edema Treatment (Latakia University Journal -Medical Sciences Series, 2021)
Purpose To study effectiveness of Intravitreal Bevacizumab 2.5mg IVB alone or Bevacizumab 1.25mg in combination with 2 mg Triamcinolone Acetonide IVTA in center-involved diabetic macular edema.Patients and methods: 61 eyes enrolled in this prospective, non-randomized, comparative study ( 36 eyes were injected with IVB, 25 eyes were injected with IVTA + IVB). Evaluation of best-corrected visual acuity BCVA, central macular thickness CMT, and intraocular pressure IOP was conducted at 4,8,12 weeks after treatment.Results: Significant CMT reduction was observed in each group along the follow-up period (P